POSITIVE EMOTION RECOGNITION THROUGH EYE TRACKING TECHNOLOGY - Baharom, N.H.; Jayabalan, N.; Amin, M.K.M.; Wibirama, S. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Currently, modern eye tracking technology has been utilized to examine the gazing behavior as human visual perception is very much linked to the psychological knowledge of mental processes. Hence, eye tracking technology is potential to reveal hidden cognitive processes of human behaviour. However, eye tracking understanding can be crucial to investigate as the analysis involved the nature feeling of positive stimuli affects subjects’ emotions and soul through the eye tracking device. This experiment therefore attempt to investigate and identify the feeling utilizing the eye tracking sensor. Audio-visual setup of media containing positive emotions attributes were exhibited to participants to gauge the feeling of valence and excitement. The experiment used Tobii TX300 eye tracker with 10 subjects participated. The positive emotions that apply in this experiment are Love, Joy, Inspiration and Serenity. The results showed that both "Joy" and "Inspiration" stimuli fixation duration peaks the longest at 7000ms among the ten subjects tested. The experiment further found that the pupil dilated strongly to “Joy” and “Inspiration”. These fixation metrics results confirmed that the participants visual attention toward salient image content were differently processed which concluded the positive emotion recognition. The results sum up that eye tracking metrics is useful to implicitly uncover the feelings insight of human behavior.